2019
DOI: 10.1021/acssuschemeng.9b02494
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticles Induced an Enhanced and Intimately Coupled Photoelectrochemical-Microbial Reductive Dissolution of As(V) and Fe(III) in Flooded Arsenic-Enriched Soils

Abstract: Nanosized titanium dioxide (TiO2) is a naturally existing nanoscale semiconducting mineral, and its co-occurrence with microbes may elicit differential environmental effects. In this study, the impacts of TiO2 nanoparticles (NPs) on the reductive dissolution of As­(V) and Fe­(III) from flooded arsenic-enriched soils were examined under intermittent illumination and dark conditions. The amendment with TiO2 NPs under intermittent illumination resulted in the highest As/Fe reduction among all amendments. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Importantly, Fe(III) dissolution was promoted by intermittent illumination compared to dark conditions. We attributed this response to enhanced production of photoelectrons originating from the illuminated endogenous minerals that then flowed into microbial extracellular electron transfer chains (Chen et al, 2019b). MnO 2 -ammended soils showed a sharp decrease in reductive dissolution of Fe(III) and demonstrated a dose-dependent response.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, Fe(III) dissolution was promoted by intermittent illumination compared to dark conditions. We attributed this response to enhanced production of photoelectrons originating from the illuminated endogenous minerals that then flowed into microbial extracellular electron transfer chains (Chen et al, 2019b). MnO 2 -ammended soils showed a sharp decrease in reductive dissolution of Fe(III) and demonstrated a dose-dependent response.…”
Section: Resultsmentioning
confidence: 97%
“…2). Thus, we inferred that a greater amount of photoelectrons excited from exogenous semiconducting MnO 2 particles were supplied to promote the higher reductive dissolution of As(V)/Fe(III) in the intermittently illuminated assays (Chen et al, 2019b). Additional evidence for this supposition resulted from a greater decline of fluorescence signals, corresponding to the heavy-molecular-weight humic/ fulvic acids-like compounds, in the intermittent illumination versus dark treatments (Fig.…”
Section: Regulation Of Microbial Doc Consumption By Mno 2 Particlesmentioning
confidence: 84%
“…The study on the natural BPEC systems at the water-sediment interface is at a very early stage and mainly focuses on the metal elements. It was reported that the photo-excited mineral photoelectrons from various SQDs such as ZnS, MnO 2 and TiO 2 , participated in the microbial electron transfer chain for As/Fe reduction in flooded soils, and the synchronously excited photoholes could be scavenged by humic/fulvic acids (Dong et al, 2021;Chen et al, 2019cChen et al, , 2019d. The introduction of these SQDs would increase the electrical conductivities of soil particles and enhance the production of c-type cytochrome, thereby enabling a long-distance photoelectron transfer.…”
Section: Understanding Of Biogeochemical Cycle Of Elements At the Water-sediment Interfacementioning
confidence: 99%
“…This phenomenon is widely discovered in both natural and artificial environments. The former can occur in mineral coating (Lu et al, 2012), flooded soils (Chen et al, 2019c(Chen et al, , 2019d, and offshore areas (Liu et al, 2020) for the specific biogeochemical redox processes due to the widespread existence of electrotrophs (e.g., Acidithiobacillus ferrooxidans, Alcaligenes faecalis, S. oneidensis and Geobacter metallireducens) and natural semiconductor minerals (e.g., rutile [TiO 2 ], sphalerite [ZnS], and goethite [FeOOH]). The latter holds a great potential for pollutant control and energy production in engineered systems like biological wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…illumination [118,119]. Notably, there was improved bacterial viability in biofilms and high enrichment of Geobacteraceae (a nearly 1.5-fold increase of relative abundance vs. control) in a photobioanode that was equipped with hematite [120].…”
Section: Alternative Photoelectrotrophy Microbial Metabolism Favored mentioning
confidence: 98%